Observatory Of Teacher Training In The Context Of Arts Teaching: Some Reflections - Oliveira, Uillian Trindade; Vago-Soares, Maria Angélica; Camargo, Fernanda Monteiro Barreto; Monteiro, Thalyta (Farol, 2024)
The article reflects and analyzes art teaching, learning in Art and teaching work, from a historical-cultural perspective, focusing on the teaching training of Art teachers and contemporary ways of teaching and learning, as well as thinking about issues that permeate the appreciation of teaching. The study is connected to three (3) questions — numbered fifteen (15), eighteen (18) and thirty (30) — which are among the 41 questions answered by 737 Art teachers about the working conditions of Art teachers and the use of textbooks for teaching art. The focus of the article is on human formation, on the memories and experiences of the subjects involved in teaching and learning Art. The main theoretical references used were: Vigotski (2007), to reflect on the processes of mediation between man and the world from a historical-cultural perspective and Brandão (2003), to think about multi-handed research and the processes of teaching and learning without a single holder of knowledge.